English nominal clauses and their Vietnamese translation version in “Gone with the wind” novel / Lê Thái Hòa; NHDKH Assoc.Prof.Dr Hoàng Tuyết Minh - Lê, Thái Hòa
This study is aimed at describing the features of English nominal clauses in “Gone with the wind” and their Vietnamese translation versions to find out the differences and similarities of nominal clauses in the two languages in order to offer suggestions for teaching English nominal clauses to Vietnamese learners. To conduct this thesis, the writer has a need of using three mainly methods: Descriptive method is used to describe the syntactic and semantic features of nominal clauses in English, Comparative method is used to find out the similarities and differences between nominal clauses in English with reference to the Vietnamese equivalents, and Quantitative and Qualitative method is used to investigate theoretical background and framework of the study, as well as to collect the data. Basing on that, the study analyzes and explains English nominal clauses toward classifications and functions. Moreover, the study also gives out many useful examples from famous books and novels for clearness and focuses on some areas where learners often make errors for finding suitable solutions. There are so many English nominal clauses in the “Gone with the wind” novel so the examples selected in the novel as model for each type and functions. Below each function of English nominal clause, there is a table performing the word order of both languages: English and Vietnamese. The thesis has provided 96 examples of English nominal clauses from “Gone with the wind novel. The study is considered a good reference for learning and researching English language and suggestions for teaching and learning English nominal clause as well as realize the importance of English nominal clauses in teaching so that they can adapt them to their own teaching conditions.